## 17Calculus - Differential Equations - First Order Practice

##### 17Calculus

This page contains a mixed bag of practice problems solving first order differential equations based on a video from one of our favorite instructors. We have laid out each practice problem and included the video clip containing each solution.
We recommend that you download this pdf of his list of problems before starting. However, his videos do not follow this pdf exactly.

Make sure you support the guy that did this video. He put a LOT of work into, not just doing the video, but also preparing the problems and making sure his solutions were correct. He did a GREAT job. So go to YouTube and like this video and follow him. He is one of our favorite instructors. (By the way, we are not receiving any compensation from him. We just think his videos will help you.) Here is his YouTube channel link.

Practice

Find the general solution to these differential equations. If initial conditions are given, find the particular solution as well.

Basic

$$(\sin(y) - y\sin(x))dx + (\cos(x)+x\cos(y))dy = 0$$

Problem Statement

$$(\sin(y) - y\sin(x))dx + (\cos(x)+x\cos(y))dy = 0$$

Solution

### blackpenredpen - 3664 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$(4x^2-10y)dx + (2x^3/y-15x)dy = 0, y(2) = -1$$

Problem Statement

$$(4x^2-10y)dx + (2x^3/y-15x)dy = 0, y(2) = -1$$

Hint

This is almost exact. Use the special integrating factor $$\mu(x,y) = x^m y^n$$

Problem Statement

$$(4x^2-10y)dx + (2x^3/y-15x)dy = 0, y(2) = -1$$

Hint

This is almost exact. Use the special integrating factor $$\mu(x,y) = x^m y^n$$

Solution

### blackpenredpen - 3665 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$dy/dx = \cos(x) - y\sec(x), y(0) = 2$$

Problem Statement

$$dy/dx = \cos(x) - y\sec(x), y(0) = 2$$

Solution

### blackpenredpen - 3666 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$(xy + y^2 + x^2)dx - x^2dy = 0$$

Problem Statement

$$(xy + y^2 + x^2)dx - x^2dy = 0$$

Solution

### blackpenredpen - 3667 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$(2x+\cos y)dx + (x^2 + \tan y + \cos^2 y)dy = 0$$

Problem Statement

$$(2x+\cos y)dx + (x^2 + \tan y + \cos^2 y)dy = 0$$

Solution

### blackpenredpen - 3668 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$\displaystyle{ (x^2+1)\frac{dy}{dx} + xy - x = 0 }$$

Problem Statement

$$\displaystyle{ (x^2+1)\frac{dy}{dx} + xy - x = 0 }$$

Solution

### blackpenredpen - 3669 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$dy/dx = 2-\sqrt{ 2x-y+3 }$$

Problem Statement

$$dy/dx = 2-\sqrt{ 2x-y+3 }$$

Solution

### blackpenredpen - 3670 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$2xye^{x^2} dx + (e^{x^2}- 1/y)dy = 0$$

Problem Statement

$$2xye^{x^2} dx + (e^{x^2}- 1/y)dy = 0$$

Solution

### blackpenredpen - 3671 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$e^y dx - e^x dy = 0, y(0) = 0$$

Problem Statement

$$e^y dx - e^x dy = 0, y(0) = 0$$

Solution

### blackpenredpen - 3672 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$dy/dx = -y(1+xy^2), y(0) = 1/2$$

Problem Statement

$$dy/dx = -y(1+xy^2), y(0) = 1/2$$

Solution

### blackpenredpen - 3673 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$(y^2-x^2)dx - xydy = 0, y(1) = 3$$

Problem Statement

$$(y^2-x^2)dx - xydy = 0, y(1) = 3$$

Solution

He works this several different ways. Make sure to watch the complete video so that you can learn how to solve this in more ways than one.

### blackpenredpen - 3674 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$dP/dt = P(a-b\ln P), P(0) = P_0$$

Problem Statement

$$dP/dt = P(a-b\ln P), P(0) = P_0$$

Solution

### blackpenredpen - 3675 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$dP/dt = kP(1-P/M), P(0) = P_0$$

Problem Statement

$$dP/dt = kP(1-P/M), P(0) = P_0$$

Solution

### blackpenredpen - 3678 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$\displaystyle{ \frac{dy}{dx} = \frac{x-y}{x+y} }$$

Problem Statement

Find the general solution to the differential equation $$\displaystyle{ \frac{dy}{dx} = \frac{x-y}{x+y} }$$

Solution

Here are two videos by two different instructors with similar solutions to this differential equation.

### SyberMath - 3679 video solution

video by SyberMath

### blackpenredpen - 3679 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$dy/dx= \sqrt{y} - y$$

Problem Statement

$$dy/dx= \sqrt{y} - y$$

Solution

### 3680 video solution

Log in to rate this practice problem and to see it's current rating.

$$\displaystyle{ dy/dx = \frac{1-2y-\sin^2(x^2y)}{x} }$$

Problem Statement

$$\displaystyle{ dy/dx = \frac{1-2y-\sin^2(x^2y)}{x} }$$

Solution

### blackpenredpen - 3681 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$(-3y+ x^2y^2)dx + (x-2x^3y+x^4/y)dy = 0$$

Problem Statement

$$(-3y+ x^2y^2)dx + (x-2x^3y+x^4/y)dy = 0$$

Solution

### blackpenredpen - 3682 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$2xye^{x^2}dx + (e^{x^2}-1/y)dy = 0$$

Problem Statement

$$2xye^{x^2}dx + (e^{x^2}-1/y)dy = 0$$

Solution

### blackpenredpen - 3684 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$\displaystyle{ y' = -x + \frac{1}{2x}y, y(1) = 0 }$$

Problem Statement

$$\displaystyle{ y' = -x + \frac{1}{2x}y, y(1) = 0 }$$

Solution

### blackpenredpen - 3685 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$y' = x^2 + 2xy + y^2, y(1) = 0$$

Problem Statement

$$y' = x^2 + 2xy + y^2, y(1) = 0$$

Solution

### blackpenredpen - 3687 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

Intermediate

$$\displaystyle{ dy/dx = \frac{xy^2-\sin x \cos x}{y(1-x^2)}, y(0) = 4 }$$

Problem Statement

$$\displaystyle{ dy/dx = \frac{xy^2-\sin x \cos x}{y(1-x^2)}, y(0) = 4 }$$

Solution

### blackpenredpen - 3677 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$\displaystyle{ y' = -x + \frac{1}{2x}y + y^2, y(1) = 0 }$$

Problem Statement

$$\displaystyle{ y' = -x + \frac{1}{2x}y + y^2, y(1) = 0 }$$

Hint

Start with $$y_1 = x^n$$ and find $$y = y_1 + v$$

Problem Statement

$$\displaystyle{ y' = -x + \frac{1}{2x}y + y^2, y(1) = 0 }$$

Hint

Start with $$y_1 = x^n$$ and find $$y = y_1 + v$$

Solution

### blackpenredpen - 3686 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$y = \left( \dfrac{dy}{dx} \right)^2$$

Problem Statement

Solve the differential equation $$y = \left( \dfrac{dy}{dx} \right)^2$$

Solution

### SyberMath - 4346 video solution

video by SyberMath

Log in to rate this practice problem and to see it's current rating.

$$y = xy' + \sqrt{(y')^2 + 1}$$

Problem Statement

$$y = xy' + \sqrt{(y')^2 + 1}$$

Hint

Start by taking the derivative of the original differential equation.

Problem Statement

$$y = xy' + \sqrt{(y')^2 + 1}$$

Hint

Start by taking the derivative of the original differential equation.

Solution

### blackpenredpen - 3676 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

$$y=xy'-e^{y'}$$

Problem Statement

$$y=xy'-e^{y'}$$

Solution

### blackpenredpen - 3683 video solution

video by blackpenredpen

Log in to rate this practice problem and to see it's current rating.

When using the material on this site, check with your instructor to see what they require. Their requirements come first, so make sure your notation and work follow their specifications.

DISCLAIMER - 17Calculus owners and contributors are not responsible for how the material, videos, practice problems, exams, links or anything on this site are used or how they affect the grades or projects of any individual or organization. We have worked, to the best of our ability, to ensure accurate and correct information on each page and solutions to practice problems and exams. However, we do not guarantee 100% accuracy. It is each individual's responsibility to verify correctness and to determine what different instructors and organizations expect. How each person chooses to use the material on this site is up to that person as well as the responsibility for how it impacts grades, projects and understanding of calculus, math or any other subject. In short, use this site wisely by questioning and verifying everything. If you see something that is incorrect, contact us right away so that we can correct it.

Links and banners on this page are affiliate links. We carefully choose only the affiliates that we think will help you learn. Clicking on them and making purchases help you support 17Calculus at no extra charge to you. However, only you can decide what will actually help you learn. So think carefully about what you need and purchase only what you think will help you.

We use cookies on this site to enhance your learning experience.